2009
DOI: 10.1016/j.jvs.2009.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temporary shunting on extremity vascular injury: An outcome analysis from the Global War on Terror vascular injury initiative

Abstract: Temporary vascular shunting used as a damage control adjunct in management of wartime extremity vascular injury does not lead to worse outcomes. Benefit from TVS is suggested, but not statistically significant. Injury specific variables of venous ligation, associated fracture, and penetrating blast mechanism are associated with amputation. Amputation-free survival after vascular injury in Operation Iraqi Freedom is 79% at three years. Further studies to statistically define any possible benefits of TVS are nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(82 citation statements)
references
References 31 publications
0
75
0
7
Order By: Relevance
“…In their study, the authors used case-controlled methodology to show that the use of temporary vascular shunts had no adverse outcome in the years following vascular repair and likely extended the window for limb salvage, especially in the most severely injured extremities. 25 Finally in a recent and larger 10-year review of the civilian experience from Feliciano's group at Grady Memorial, Subramanian et al confirmed the utility of temporary vascular shunts in certain patterns of vascular injury. This study demonstrated a 95% patency rate of shunts and an overall survival rate of 88% following major vascular injury.…”
Section: Shunt Materialsmentioning
confidence: 96%
See 2 more Smart Citations
“…In their study, the authors used case-controlled methodology to show that the use of temporary vascular shunts had no adverse outcome in the years following vascular repair and likely extended the window for limb salvage, especially in the most severely injured extremities. 25 Finally in a recent and larger 10-year review of the civilian experience from Feliciano's group at Grady Memorial, Subramanian et al confirmed the utility of temporary vascular shunts in certain patterns of vascular injury. This study demonstrated a 95% patency rate of shunts and an overall survival rate of 88% following major vascular injury.…”
Section: Shunt Materialsmentioning
confidence: 96%
“…This determination can often be aided by the use of continuous-wave Doppler. [21][22][23][24][25][26][27][28][29] In cases where there is injury to more than one of the small distal arteries (e.g., both ulnar and radial arteries) resulting in an absence of Doppler signal beyond the injury, use of a vascular shunt is recommended. 33 Those who have extensive experience with placing shunts frequently state that in the setting of penetrating vascular injury, the two ends of the severed vessel must be exposed for ligation anyway.…”
Section: Venous Shuntingmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend was greatest in patients with severely injured limbs. The authors concluded that temporary vascular shunting used as a damage control adjunct in management of wartime extremity vascular injury does not lead to worse outcomes [ 16 ]. Analyses from all available publications suggest that temporary vascular shunting is an effective technique to facilitate patient transfer and is preferable to prolonged reconstruction efforts in remote less capable locations.…”
Section: Temporary Vascular Shuntsmentioning
confidence: 99%
“…14 Lower echelons of care perform any essential immediate amputations, but every eff ort is made to initially preserve limbs when they are perfused or revascularised, often using temporary vascular shunts. 21,22 When performed, traumatic amputations are …”
mentioning
confidence: 99%